2013
DOI: 10.1155/2013/432097
|View full text |Cite
|
Sign up to set email alerts
|

Si Shen Wan Inhibits mRNA Expression of Apoptosis-Related Molecules in p38 MAPK Signal Pathway in Mice with Colitis

Abstract: Si Shen Wan (SSW) is used to effectively treat ulcerative colitis (UC) as a formula of traditional Chinese medicine. To explore the mechanism of SSW-inhibited apoptosis of colonic epithelial cell, the study observed mRNA expression of apoptosis-related molecules in p38 MAPK signal pathway in colonic mucosa in colitis mice treated with SSW. Experimental colitis was induced by 2,4,6-trinitrobenzene sulfonic acid (TNBS) in mice; meanwhile, the mice were administrated daily either SSW (5 g/kg) or p38 MAPK inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
5
18
0
Order By: Relevance
“…In the present work, TNBS boosted the apoptotic marker caspase-3, a finding that coincides with the results of previous studies [50,62]. Increased caspase-3 may be accredited, partly, to the activation of p38MAPK, where several studies proved that p38MAPK activation is responsible for apoptosis of colonic epithelial cells in UC [50]. Moreover, TNBS-induced caspase-3 may be responsible for the downregulation of PPARγ, where Guilherme et al [63] have evidenced that caspase-3 cleaves PPARγ protein and disrupts its nuclear localization.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present work, TNBS boosted the apoptotic marker caspase-3, a finding that coincides with the results of previous studies [50,62]. Increased caspase-3 may be accredited, partly, to the activation of p38MAPK, where several studies proved that p38MAPK activation is responsible for apoptosis of colonic epithelial cells in UC [50]. Moreover, TNBS-induced caspase-3 may be responsible for the downregulation of PPARγ, where Guilherme et al [63] have evidenced that caspase-3 cleaves PPARγ protein and disrupts its nuclear localization.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…In the present work, TNBS boosted the apoptotic marker caspase-3, a finding that coincides with the results of previous studies [50,62]. Increased caspase-3 may be accredited, partly, to the activation of p38MAPK, where several studies proved that p38MAPK activation is responsible for apoptosis of colonic epithelial cells in UC [50].…”
Section: Accepted Manuscriptsupporting
confidence: 92%
See 1 more Smart Citation
“…According to calculating by body surface area between human and rat, we designed dosage of SSW and projected the experimental protocol on the basis of our previous studies [ 7 – 9 ]. Ten animals were in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we observed that the antiapoptotic effect of SSW was probably realized by inhibiting mRNA expression of apoptosis-related molecules in p38 MAPK signal pathway. All results had demonstrated that SSW effectively treated colitis by inhibiting excessive apoptosis of IECs [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%